Looking from the Outside in: A Study on the International Media Coverage and Framing of Nigeria's 2019 General Election - Elega, Adeola Abdulateef; Oloyede, Felix Adedamola; Ozad, Bahire Efe (Routledge Journals, Taylor & Francis Ltd, 2021)
This study investigates the foreign media coverage of Nigeria's 2019 general election through a content analysis of news stories (n = 135) obtained from 10 international news sources. This study aims to evaluate the dominant frames that emerged in the coverage of the election as well as the tones used by the international news sources in the coverage of Nigeria's 2019 general election. Empirical evidence reveals that the political system frame, human interest/people frame, and violence frame are the major frames that emerged from the international news sources. We also found that the tone of the international media coverage of Nigeria's 2019 general election was neutral, although the sum of news stories reported in a negative and critical manner was also relatively noticeable, especially by the American news sources. Overall, we conclude that the foreign media coverage and framing of Nigeria's 2019 general election were relatively neutral, hence maintaining the time-honoured fundamental values of journalism and election coverage-balance and fairness.
Keywords: International media; media framing; Framing Theory; Nigeria; Nigeria’ s 2019 general election; content analysis